KEBENARAN DAN KERAGUAN DALAM STUDI KEISLAMAN (TELAAH PEMIKIRAN CHARLES SANDER PEIRCE DALAM BUKU CONTEMPORARY ANALYTIC PHILOSHOPHY) - Afga Sidiq Rifai (Jurnal Penelitian Agama, 2019)
Theory of belief and doubt Charles Sander Peirce gives fresh air to the problems faced by Muslims who are trapped in madzhabiyah and class fanaticism. Charles S. Peirce with the theory of Pragmatism tries to pioneer new philosophical thinking, where good theory must lead to the discovery of new facts and the consequences of theoretical thinking in practice does not stop at doctrine and truth claims (truth claim). Arguments that want to be proposed are beliefs about the truth if a test can be carried out to find truths about their beliefs that will give meaning. In religious studies the approach of Charles S. Peirce's theory is important to find the meaning of a truth that is believed. Keywords: Belief, doubt, Islamic study, Charles Sander Peirce